Total synthesis of hapalindoles J and U, formal synthesis of haplaindole O, synthesis of the proposed biosynthetic precursor to hapalindole K and work towards the ambiguine family of alkaloids - Rafferty, Ryan J., author; Williams, Robert M., advisor; Shi, Yian, committee member; Crans, Debbie C., committee member; Prieto, Amy L., committee member; Thamm, Douglas H., committee member (Colorado State University. Libraries, 2011)
Herein I discussed the total synthesis of hapalindoles J and U, the formal synthesis of hapalindole O, the proposed biosynthetic precursor to hapalindole K and efforts towards other hapalindole and ambiguine families of alkaloids. The hapalindoles and ambiguines both possess a highly functionalized 6:6:6:5, which I accessed over six synthetic steps via a developed silyl strategy with an overall 54% yield. Hapalindole J was synthesized in an overall 11% yield over eleven synthetic steps and hapalindole U in an overall 25% yield over thirteen synthetic steps from commercially available materials utilizing the silyl strategy developed. A formal synthesis of hapalindole O, intercepting Natsume's total synthesis, was accomplished as well via the developed silyl strategy. In addition, the synthesis of the proposed biosynthetic precursor to hapalindole K was accessed. Currently, this newly developed silyl strategy is being employed in accessing some of the more functionalized hapalindoles (such as K) as well as the complex ambiguine core.
Keywords: ambiguine; total synthesis; silyl; hapalindole